Fast custom apparel design and simulation for future demand-driven manufacturing. Issue 2 (4th November 2019) - Jiang, Zhenbin; Guo, Juan; Zhang, Xinyu
Abstract : Purpose: A common pipeline of apparel design and simulation is adjusting 2D apparel patterns, putting them onto a virtual human model and performing 3D physically based simulation. However, manually adjusting 2D apparel patterns and performing simulations require repetitive adjustments and trials in order to achieve satisfactory results. To support future made-to-fit apparel design and manufacturing, efficient tools for fast custom design purposes are desired. The purpose of this paper is to propose a method to automatically adjust 2D apparel patterns and rapidly generate acustom apparel style for a given human model. Design/methodology/approach: The authors first pre-define a set of constraints using feature points, feature lines and ease allowance for existing apparels and human models. The authors formulate the apparel fitting to a human model, as a process of optimization using these predefined constraints. Then, the authors iteratively solve the problem by minimizing the total fitting metric. Findings: The authors observed that through reusing existing apparel styles, the process of designing apparels can be greatly simplified. The authors used a new fitting function to measure the geometric fitting of corresponding feature points/lines between apparels and a human model. Then, the optimized 2D patterns are automatically obtained by minimizing the matching function. The authors' experiments show that the authors' approach can increase the reusability of existing apparel styles and improve apparel design efficiency. Research limitations/implications: There are some limitations. First, in order to achieve interactive performance, the authors' current 3D simulation does not detect collision within or between adjacent apparel surfaces. Second, the authors' did not consider multiple layer apparels. It is non-trivial to define ease allowance between multiple layers. Originality/value: The authors use a set of constraints such as ease allowance, feature points, feature lines, etc. for existing apparels and human models. The authors define a few new fitting functions using these pre-specified constraints. During physics-driven simulation, the authors iteratively minimize these fitting functions.